From Hunger Levels to Resilience Trajectories: A Dynamic Resilience Framework for Food Security - Reuveni, Saada (Technium Social Sciences Journal, 2026)
This article develops a Dynamic Resilience Framework (DRF) to conceptualize hunger and food security as trajectories rather than static conditions. Building on earlier distinctions between one-dimensional (availability-focused) and multi-dimensional (FAO’s four pillars) hunger solutions, it argues that existing frameworks largely diagnose levels of food security but do not explain how and why countries move between states of vulnerability and resilience over time. Drawing on resilience theory, research on the informal economy, and critical work on data and humanitarian governance, the DRF conceptualizes food systems as evolving through three interconnected stages: Crisis and Shock Response, Adaptive Recovery, and Transformative Resilience. It positions Adaptive Informal Food Commons (AIFC)-informal markets, neighborhood networks, and community feeding systems- as meso level engines of crisis coping and innovation, and embeds a Bias-Transparency-Trust (BTT) lens to highlight how governance and data practices condition the legitimacy and impact of interventions. The article specifies a conceptual state-transition and determinant model and derives propositions on the roles of infrastructure, digital inclusion, women’s financial access, informality, and governance in shaping upward transitions. It concludes with a research agenda and argues that moving from levels to trajectories is essential for designing sequenced, transition-oriented strategies to end hunger.